PERILAKU ENJOKOUSAI DALAM NOVEL GROTESQUE KARYA NATSUO KIRINO - Andani Pertiwi, I Gusti Ayu (Humanis, 2017)
This research entitled “Enjokousai in Grotesque Novel by NatsuoKirino”.The theories used for analyzing areliterature sociology theory by Wallek Warren and social pathology theory by Kartono. This research aims to find out the type of enjokousai, causative factor, and the impact of enjokousai in Grotesque novel by Natsuo Kirino. Based on the analysis that has been done, there are two types of enjokousai, such as enjokousai by joining the group and enjokousai by not joining the group. Enjokousai is caused by internal and external factors, such as hipersexual, economic consideration to survive, in childhood had sexual intercourse,compensation of inferiority feeling, the assumption that women are needed in the game of love. There are also four impacts of enjokousai, such as damage the household, damage the moral and law, cause human exploitation, and cause sexual dysfunction.
Keywords: sexuality, enjokousai, deviant behavior